Developing Quality Standards and Performance Measures for Residential Group Care: Translating Theory to Practice. Issue 4 (2nd October 2019) - Boel-Studt, Shamra; Huefner, Jonathan C.; Bender, Kenneth; Huang, Hui; Abell, Neil
ABSTRACT: With the increased emphasis on accountability at the federal and state levels, efforts to identify and address issues impacting the quality and effectiveness of residential care programs are needed. Establishing quality practice standards with measurable performance indicators is a useful means for promoting and evaluating the quality of care in residential programs and informing a process of continuous quality improvement. In this article, we describe a state-wide initiative to enhance the quality of residential group care in Florida. Specifically, we describe efforts to establish a set of quality standards for residential programs and to operationalize the standards by developing and piloting an assessment designed to measure the extent to which group home practices align with the standards. In addition to describing steps taken, we highlight important conceptual and practical considerations for translating standards generated from extant research, best practices, and field experts into clearly defined domains and measurable standards that can be meaningfully transported into a complex practice setting. Finally, we discuss lessons learned and recommendations that may guide similar efforts beyond the state of Florida.